1995
DOI: 10.1016/0014-5793(95)01066-n
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and characterization of human thioltransferase (glutaredoxin) in E. coli

Abstract: PCR primers were designed from the known amino acid (aa) sequence for human red blood cell thioltransferase (hRBC TTase) and the known cDNA sequence for pig liver TTase (82% homologous) and used to amplify thioltransferase from a pool of human brain cDNAs. The PCR product was inserted into the pKK233-2 expression vector. The DNA sequence of the insert agreed with the aa sequence. High level expression of the enzyme was accomplished in E. coli, and Western blot analysis confirmed its identity. Recombinant TTase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 18 publications
(27 reference statements)
1
38
0
Order By: Relevance
“…Previous studies have shown that GRX contains two redox-active cysteine residues, Thr-Cys 22 -Pro-Tyr-Cys 25 -Arg in an active catalytic center (42). However, unlike TRX, GRX is highly selective for glutathione-containing disulfides, and its catalytic cycle involves a covalent glutathionyl-enzyme disulfide intermediate (GRX-SSG) rather than an intramolecular disulfide at its active site (31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that GRX contains two redox-active cysteine residues, Thr-Cys 22 -Pro-Tyr-Cys 25 -Arg in an active catalytic center (42). However, unlike TRX, GRX is highly selective for glutathione-containing disulfides, and its catalytic cycle involves a covalent glutathionyl-enzyme disulfide intermediate (GRX-SSG) rather than an intramolecular disulfide at its active site (31).…”
Section: Discussionmentioning
confidence: 99%
“…Glutaredoxins catalyze the cleavage of mixed disulfides in the presence of low concentrations of GSH and may therefore protect cells by reducing any mixed disulfides formed during oxidative stress (Chrestensen et al, 1995). In addition, in vitro experiments indicate that glutaredoxins can reactivate a number of oxidized enzymes by reducing the mixed disulfides formed as a result of thiol oxidation (Terada et al, 1992;Terada, 1994;Yoshitake et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Thioredoxin reductase (bovine and Escherichia coli) was purchased from Sigma and American Diagonstica (Greenwich, CT Enzymes-Recombinant human thioltransferases (wild type and mutant) were expressed and purified from E. coli as described previously (5,27). The thioltransferase enzymes and bovine GSSG reductase were diluted in PGN buffer (100 mM sodium/potassium phosphate, pH 7.5, 0.5 mM GSH, and 0.2 mM NADPH) for inhibition experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Transfection-The hygromycin-resistant, constitutively active expression vectors pRep4 and pRep10 were modified by insertion of thioltransferase cDNA (27) into the multicloning region (identical but reversed in the two plasmids) between the BamHI and HindIII sites to construct sense (pRep 10) and antisense (pRep 4) plasmids. Transfection was accomplished with Lipofectamine using manufacturer's protocols, and cells were photographed at 6 weeks.…”
Section: Methodsmentioning
confidence: 99%